Susceptibilities of clinical Clostridium difficile isolates to antimicrobials: a systematic review and meta-analysis of studies since 1970. (February 2018) - Khanafer, N.; Daneman, N.; Greene, T.; Simor, A.; Vanhems, P.; Samore, M.; Brown, K.A.
Abstract: Objectives: Although exposure to antibiotics can cause Clostridium difficile infection, certain antibiotics are used to treat C. difficile . Measurements of antimicrobial C. difficile activity could help to identify antibiotic risk and emergent resistance. Here, we describe publication patterns relating to C. difficile susceptibilities and estimate minimum inhibitory concentrations (MIC) for antibiotic classes in the published literature between January 1970 and June 2014. Methods: We queried PUBMED and EMBASE for studies reporting antibiotic C. difficile MIC in English or French. We used mixed-effects models to obtain pooled estimates of antibiotic class median MIC (MIC50 ), 90th percentile of MIC (MIC90 ), and MIC90 :MIC50 ratio. Results: Our search identified 182 articles that met our inclusion criteria, of which 27 were retained for meta-analysis. Aminoglycosides (MIC50 120 mg/L, 95% CI 62–250), 3rd (MIC50 75 mg/L, 95% CI 39–130) and 2nd generation cephalosporins (MIC50 64 mg/L, 95% CI 27–140) had the least C. difficile activity. Rifamycins (MIC50 0.034 mg/L, 95% CI 0.012–0.099) and tetracyclines (MIC50 0.29 mg/L, 95% CI 0.054–1.7) had the highest level of activity. The activity of 3rd generation cephalosporins was more than three times lower than that of 1st generation agents (MIC50 19 mg/L, 95% CI 7.0–54). Time-trends in MIC50 were increasing for carbapenems (70% increase per 10 years) while decreasing for tetracyclines (51% decrease per 10 years). Conclusions: We found a 3500-fold variation in antibiotic C. difficile MIC50, with aminoglycosides as the least active agents and rifamycins as the most active. Further research is needed to determine how in vitro measures can help assess patient C. difficile risk and guide antimicrobial stewardship.